Toxicidad de los extractos de las semillas de Erythrina americana - García Mateos, Rosario; Soto Hernández, Marcos; Martínez Vázquez, Mariano (CIENCIA ergo-sum; Vol. 7 Núm. 2 (2000): CIENCIA ergo-sum (julio-octubre 2000), 2015)
-